The Influence Of Fear Of Missing Out (Fomo), Live Streaming, And Flash Sales On Impulsive Buying Of Hulm Fashion Products Among Generation Z On Tiktok Shop In Surabaya - Prilga Westrin Kusumaningrum; Indah Respati Kusumasari (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to examine the influence of Fear of Missing Out (FoMO), live streaming, and flash sale on impulsive buying behavior of fashion products, specifically the HULM brand, among Generation Z consumers on TikTok Shop in Surabaya. A quantitative approach was employed using a survey method with a Likert scale questionnaire distributed to respondents who have experience purchasing HULM products through TikTok Shop. The collected data were analyzed using multiple linear regression to determine both simultaneous and partial effects of the independent variables on impulsive buying behavior. These results suggest that impulsive buying behavior among Generation Z is shaped by both psychological factors and digital marketing strategies. FoMO acts as an internal driver, while live streaming and flash sale function as external stimuli that reinforce purchasing impulses. This study contributes to the development of consumer behavior literature, particularly in the context of social commerce, and offers practical insights for marketers in designing effective promotional strategies on TikTok Shop to better target Generation Z consumers.